Child mental health: a developmental approach from Kurdistan - Ahmad, Abdulbaghi (Henry Stewart Talks, 2018)
Child mental health definition, Multidisciplinary scientific field, Introducing for the first time in Kurdistan in 1991, Collaboration with Sweden, Identifying cultural protecting and risk factors, Increasing needs following the increasing public awareness, Research results leading to academic unit establishment, Building up local competence at three levels, Service systems including governmental and private sectors